ISSUE OF GERMAN GUILT IN THE PHILOSOPHY OF KARL JASPERS - Pykalo, Andrii O. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2020)
The main research aspect of the article is the “issue of guilt”, i. e. Germany’s responsibility for the establishment of Nazism and the outbreak of World War II in the philosophical legacy of the German existentialist philosopher Karl Jaspers. The article analyzes the ideas of K. Jaspers on the need to realize and admit guilt for their crimes by the German people and to overcome the totalitarian legacy. K. Jaspers emphasizes that the German people must be held accountable for the crimes of the Nazi regime in the 1930s and 1940s. Jaspers addresses the issue of morality and identifies four types of guilt. The first type is criminal guilt, which lies on those who have committed criminal offenses. The second type is political guilt. The third type is moral guilt. The last, fourth type is metaphysical guilt which is associated with a sense of responsibility for every wrong and unjust act in the world. For the author, the last two types of guilt are of the greatest importance. Thus, the tragedy of World War II and the ethnic genocides committed by the Nazis were the result of moral and ethical problems and the general spiritual crisis of the German people. The key role is given to the metaphysical aspect of this crisis. It is claimed that it was the spiritual problems that gave rise to the irreversible processes in the development of the entire nation. The paramount importance of the phenomenon of collective thinking is denied, giving preference to the personal level. It is noted that the main condition for spiritual revival is the rejection of national illusions, an unbiased view of one’s own past and present life, the recognition of one’s own sin, without which repentance of both the nation and the individual is impossible. Of great importance is the aspect of humility, which functions as “our spiritual essence”, which leads to the fact that man is on the path of perfection, which ultimately leads him to God. It is emphasized that the admission of guilt and remorse is a vital necessity for the German people. The article also highlights the impact of Jaspers’ ideas on the formation of modern humanitarian policy in the Federal Republic of Germany.